The mediation effect of human capital on the relationship between senior entrepreneurial competency and entrepreneurial performance using mediation model - Do Hui Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: This study analyzed the mediation effect of human capital on the relationship between entrepreneurial competency and entrepreneurial performance using mediation model. Design/methodology/approach: This study was designed as a conceptual research model to verify the mediation effect of human capital on the relationship between entrepreneurial competency and entrepreneurial performance using mediation model. In order to design a conceptual research model, a total 24 items were investigated and the SEM method was verified using three latent variables. Findings: According to this study, human capital acted as a mediating effect in the relationship between entrepreneurial competency and entrepreneurial performance. This means that entrepreneurial competency has a direct effect on entrepreneurial performance and at the same time has an indirect effect through human capital, which means that it does not act as a partial mediating effect, but acts as a complete mediating effect through human capital. Research limitations/implications: The policy implications of this study are that it is necessary to create a virtuous cycle of the startup ecosystem of senior entrepreneurs by building and utilizing the human capital possessed by senior entrepreneurs, and the practical implications are that senior entrepreneurs must develop their entrepreneurial competency well to increase entrepreneurial performance. This is important, but more than anything, entrepreneurial performance increases when the human capital of senior entrepreneurs is actively utilized. In the process of carrying out this study, limited discussions were held on the selection of the sample to be investigated, the establishment of the research model and hypothesis, and the operational definition and measurement of variables. These issues need to be reflected in future research to improve the research. Originality/value: The main contribution of this study is to apply the dynamic capability theory to senior entrepreneurs to find that senior entrepreneurs strengthened their entrepreneurial competency through seizing, sensing, and transforming to increase entrepreneurial performance, and also to create a virtuous cycle in the senior startup ecosystem. The value of this study is that it found the importance of human capital to create a structure.
Keywords: 650; Entrepreneurial competency; Human capital; Entrepreneurial performance; Partial mediation model; Completed mediation model